Penyelesaian Kredit Bermasalah Pada PT. Bank BTPN MUR Tbk. Cabang Solo - Tanzil, Andriyanto; , Anton Agus Setyawan, SE., M.Si; , Drs. Wiyadi, M.M., Ph.D (2015)
This study aims to discuss three issues, namely how the process of resolving problem loans through litigation and non-litigation, what factors are used for the settlement of non-performing loans, the obstacles encountered in the completion of the Bank's non-performing loans in the Bank BTPN Branch Solo. This study used a qualitative descriptive method using a case study approach to PT Bank Tabungan Pensiunan Nasional (BTPN) Branch Solo. Standard completion of nonperforming loans and credit of internal control, without involving figures.The result isthatthe process ofsettlement ofnon-performing loansinthe BankBTPNBranchSolocan bedone throughlitigationistofile a lawsuitinstate courtorcommercial court, with thenon-litigationsettlementisby loweringlikemortgage interest, mortgage interestarrearsreduction, extension of timecreditandsettle or close theexisting creditat the bank. Factorsthat causeBankBTPNBranchSolochoosethe path ofnon-litigationin resolving theproblem loansistime, asifthroughlitigationtakesa longtime, the costsettlementprocessthroughlitigationrequiresa lotof funds. Results achievedwhenthroughcreditingnon-litigationdispute resolutioncanobtainmaximum results, good faithreasons for choosingnon-litigationpathwayisstillno willingnesson the part ofthe debtortosettlehis credit. Ability to paya re-analysisconductedturnsdebtor's businessis stillrunningandallow thefacilitywill be repaid.While thenon-litigationsettlement through theobstacleisbad faithof thedebtor, the debtor'slack ofawarenessofcompletingthe loanfacility, timelinessduetoinaccuratedebtorto repay the loanresulted inthe settlementbecomesprotracted, so that the burdenondebtorsgreaterresponsibility. Keywords: Nonperforming loans, Litigation, Non Litigation